Case report: Transcatheter edge-to-edge repair after prior surgical tricuspid annuloplasty - Afzal, Shazia; Haschemi, Jafer; Bönner, Florian; Kelm, Malte; Horn, Patrick (Frontiers in Cardiovascular Medicine, 2022)
Residual and recurrent tricuspid regurgitation may occur frequently after surgical tricuspid valve repair. However, reoperation for tricuspid regurgitation is rare, although many patients are again highly symptomatic. Tricuspid transcatheter edge-to-edge repair (TEER) is a promising therapy for severe tricuspid regurgitation. Herein, we report a 77-year-old woman with recurrent symptomatic massive tricuspid regurgitation 2 years after sutured annuloplasty of the tricuspid valve. TEER was successfully performed using the TriClip device and tricuspid regurgitation was reduced to a mild degree. In conclusion, tricuspid TEER is feasible following surgical suture annuloplasty. TEER is an alternative option for patients with a failed previous annuloplasty repair for tricuspid regurgitation to undergo a less invasive treatment rather than a potentially higher-risk reoperation.